Reform reversal in former transition economies (FTEs) of the European Union: Areas, circumstances and motivations - István P. Székely; Melanie Ward-Warmedinger (Institute of Labor Economics (IZA), 2018)
The rapid journey from central planning to EU (euro area) membership stress-tested the social learning processes of the Former Transition Economies (FTEs). The desire for a higher standard of living, to be anchored to the West, and to enter the EU, spurred major reform waves and led to the very rapid introduction of best-practice institutions. Although social learning accompanied this process, in many FTEs it was not fast enough to keep pace with the rapid reforms, leaving best-practice institutions with social norms that were not sufficiently strong to maintain them. As a result, wide-spread reform reversals emerged in the region. Such reform reversals appeared as formal reversals, which changed legislation (or formal rules), and behavioral reversals, which eroded the quality of an institution by materially changing the way it worked. It was frequently the interaction of reversals in different sectors that created a full-blown reform reversal episode, with the financial sector particularly prone to behavioral reversals, both in public and private institutions. External anchors such as the Washington institutions played a dominant role in shaping the transition process. Along with the EU accession process, the EU acted as a strong anchor that could prevent or reverse formal reform reversals in areas covered by EU law, but could play a much weaker role in the case of behavioral reversals. Our analysis naturally leads to the conclusion that the ultimate solution to prevent reform reversals is to accelerate social learning processes that strengthen the national ownership of reforms. It is also important to focus on the quality and internal coherence of reforms and newly created institutions.
Keywords: E6; H5; G2; J48; O5; P2; 330; reform reversals; social norms; institution building; European Union; transition economies